The politics of regional security threat in Nigeria - Sule, Babayo; Bashir Sa’ad Ibrahim,; Muhammad Yusuf Adamu, (Penerbit Universiti Kebangsaan Malaysia, 2022)
The study is an examination of the politicisation of security threats regionally in Nigeria, where all the six geo-political zones are currently involved in one form of security threat or the other, and the overall effect is a threat to national security and continuous co-existence. Nation-states strive to protect their territory by taking diligent care of security threats. One territory that failed to take adequate care of its political and socioeconomic security threats in Nigeria and that has manifested in the debilitating national and regional security threats that it is currently facing, which threaten to collapse the country. This study investigated how security issues are politicised regionally in Nigeria, where the six geopolitical zones in the country are all beleaguered with variant trends of insecurity ranging from Niger Delta militants to Boko Haram insurgents, farmers-herders clashes, rural banditry, and kidnapping, IPOB secessionist agitators and Igboho’s separatist movement. The study used a qualitative case study approach where data were derived from both primary and secondary sources. The primary source was the specialised interview with identified relevant informants, while the secondary source consisted of documented materials. The data obtained were analytically coded, discussed and interpreted using content analysis. The study discovered that Nigeria is in a ‘Hobbesian Warre of all against all’ with all the six geopolitical zones involved in one form of guerrilla warfare or the other and the nature of the threats are different in some instances, state failure while in other cases, politicised. The study recommends among others, that the Nigerian State must approach all the regional security threats with a decisive action to avoid the collapse of the remnants of the state apparatus.